Toward an Efficient Resolution for a Single-machine Bi-objective Scheduling Problem with Rejection - Moghaddam Atefeh; Teghem Jacques; Tuyttens Daniel; Yalaoui Farouk; Amodeo Lionel (Foundations of Computing and Decision Sciences, 2019)
We consider a single-machine bi-objective scheduling problem with rejection. In this problem, it is possible to reject some jobs. Four algorithms are provided to solve this scheduling problem. The two objectives are the total weighted completion time and the total rejection cost. The aim is to determine the set of efficient solutions. Four heuristics are described; they are implicit enumeration algorithms forming a branching tree, each one having two versions according to the root of the tree corresponding either to acceptance or rejection of all the jobs. The algorithms are first illustrated by a didactic example. Then they are compared on a large set of instances of various dimension and their respective performances are analysed.